Glicerina, antioxidantes e carotenóides sobre a qualidade e traçabilidade da carne de bovinos e ovinos - Zawadzki, Fernando (2013)
In this study two experiments were conducted. Exp. 1 evaluated the effects of partial replacement of corn grain by glycerine (812 g of glycerol per kg/DM) and the addition of functional oils (cashew and castor oil) extracted of plants grown in northern Brazil; and Exp. 2 evaluated the effects of a diet rich in carotenoid with low (L, 100 g/lamb/day) and high-level (H, 400 g/lamb/day) of barley supplementation during 75 days of confinement before slaughter. In Exp. 1, animal performance, feed intake, apparent digestibility, carcass characteristics, quality of the Longissimus muscle, fatty acid composition of perirenal fat, subcutaneous and Longissimus muscle fat were evaluated of Purunã bulls finished in feedlot. The corn grain was replaced by glycerine at 203 g/kg of DM/day and/or by functional oils at a dose of 3 g/animal/day. 32 8- month-old Purunã bulls (¼ Aberdeen Angus + ¼ Caracu + ¼ Charolaise + ¼ Canchim) were used, weighing 206.1 kg (SD 20.0) and finished for 252 days in feedlots. The following diets were tested: without glycerine (CON), with functional oils (FOL), with glycerine (GLY) and with glycerine + functional oils (GFO). The hot carcass weight and the hot carcass dressing were higher for the animals fed the FOL, GLY and GFO (+ 5.0% and + 3.7%, respectively) diets compared to those fed the CON diet. Diets with glycerine improved dry matter conversion (+ 8.9%) in relation to diets without glycerine. The GLY and GFO diets reduced the neutral detergent fibre intake (10.0 and 18.9%) in comparison to the CON and FOL diets, respectively. Diets did not change lauric, myristic and palmitic acids on Longissimus muscle and subcutaneous fat. FOL diet increases the content of steraric acid (+ 15.3% vs. GLY and GFO), α-linolenic (+ 27.7% vs. GFO), saturated fatty acids (+ 6.78% vs. GLY), polyunsaturated fatty acid (+ 34.4% vs. GFO), and decreases monounsaturated fatty acids (- 10.0% vs. GLY and GFO) on Longissimus muscle. Diets with glycerine reduced linoleic acid (- 21.6% vs. CON and FOL) on Longissimus muscle. Diets containing glycerine and functional oils did not change animal performance; furthermore, they improved carcass weight, feed intake and apparent digestibility. Thus, up to 20% of the DM of the diet can be replaced by glycerine with the addition of functional oils from cashew and castor plants to the diets of bulls finished in feedlot for 252 days and will provide a high-density energetic diet. In general, FO addition or not in diets without glycerine improve fatty acids on all tissues. In Exp. 2, changes in plasma carotenoid concentration, fat reflectance spectrum characteristics and color were investigated in 24 Romane male lambs kept in individual pens. Plasma carotenoid concentration at slaughter was 16% lower in H lambs than L lambs. H lambs had heavier and fatter carcasses than L lambs. Yellowness and redness of perirenal fat were slightly lower in H lambs than in L lambs. The mean absolute value of the integral (AVMI) was calculated from the reflectance spectrum of the fat in the 450?510 nm band which was not affected by the treatment. Yellowness, chroma and AVMI of subcutaneous fat were not affected by the treatment but decreased with initial live weight of animals.